Comparison of the effects of shortening rest intervals on the quality of cardiopulmonary resuscitation, physiological parameters, and hemodynamic parameters in well-trained rescuers: Randomized simulation study. Issue 6 (12th February 2021) - Kim, Dong Hun; Lee, Sang-Min; Kim, Gyun Moo; Lee, Kyung Woo; Ko, Seung Hyun; Oh, Ye Jin; Seo, Young Woo; Lee, Suk Hee; Jang, Tae Chang
Abstract: Background: Cardiopulmonary resuscitation (CPR) performance depends on individual ability and training. Well-trained or professional rescuers can maintain high-quality CPR for longer than laypeople. This study aimed to examine the effects of reducing resting intervals on CPR performance, physiological parameters, and hemodynamic parameters during prolonged CPR in well-trained providers. Methods: The study enrolled 90 volunteers from the paramedic students of our institution. They were randomly divided into 3 groups: 2 minutes, 1 minute 45 seconds, and 1 minute 30 seconds rest groups. Each participant performed 5 cycles of chest compression only CPR (2 min/cycle) with different resting intervals according to grouping. CPR quality, physiological variations, and hemodynamic variations were measured for each cycle and compared across the groups. Results: Of the 90 volunteers, 79 well-trained providers were finally included. The variation of the average chest compression depth across the 5 cycles showed significant differences between the 3 groups: from cycle 1 to 2: 1.2 (3.1) mm, –0.8 (2.0) mm, and –2.0 (3.0) mm in the 2 minutes, 1 minute 45 seconds, and 1 minute 30 seconds groups, respectively ( P  < .001); from cycle 1 to 3: 0.0 (3.0) mm, –0.7 (3.2) mm, and –2.6 (3.9) mm, respectively ( P  = .030). However, all 3 groups maintained the recommended rate and chest compression depth for all 5 cycles. Physiological and hemodynamic parameters showed no significant differences between the groups. Conclusions: Well-trained providers were able to maintain high-quality CPR despite reducing rest intervals. Adjusting the rest interval may help maintain overall CPR quality in special situations or where layperson rescuers are involved.